(untitled) (LEARNing Landscapes, 2015)
Professional development with teachers, whether they are in pre-K-12 schools or in higher education, creates opportunities for discussions among teachers and teacher educators about how to find spaces for creativity and the imagination within the structure of the Common Core State Standards, a set of national standards adopted on a stateby-state basis in the U.S. Two education faculty members and an education librarian from a large city university held workshops, bringing together university faculty in arts and humanities, science, mathematics and education, and pre-K-12 teachers to explore the potential for inquiry and creativity in the Common Core State Standards.